Pengaruh Beban Kerja Terhadap Produktivitas Mahasiswa Kelas Professional STIE IBMT Surabaya - Khofifah, Melinda (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research wants to examine further "The effect of workload on the productivity of professional class students at STIE IBMT Surabaya". The background for conducting this research is that researchers see the many phenomena of student workers who drop out and do not have the desire to carry out self-development due to the inability to balance the roles of a worker and a student. Productive students are students who can organize or manage their time well in order to do things that produce benefits both for themselves and others. The purpose of this study was to determine: the effect of workload on professional class students at STIE IBMT Surabaya. The research method in this study used quantitative research methods with a total sample of 86 respondents. The sampling technique used is purposive sampling. Retrieval of data using a questionnaire with a measuring scale of 4 Likert. The data analysis method used is validity test, reliability test, normality test, linearity test, simple regression analysis, coefficient of determination and t test. The results of this study conclude that workload has a negative and significant effect on the productivity of STIE IBMT Surabaya students, where the R Square value is 0.734 or 73.4%, the t test value is -15.238 with a significance value of 0.